MATAPU (MALAM TADARUS PUISI): INTEGRASI SENI REBANA DAN EKSISTENSI REMAJA DESA WATUALANG KEC/KAB NGAWI - Hanifah Hikmawati (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2022)
Abstract: The existence of tambourine art in the modern era can still be felt through strengthening efforts that continue to be echoed by Muslim communities in rural, urban, and Islamic boarding schools which cannot be separated from the cultural characteristics of the Indonesian people. This journal discusses the youth of Watualang village in maintaining the art of tambourine in the era of globalization and increasingly diverse social challenges. The formulation of the problem in this journal, namely; How is the existence of tambourine art for the youth of Watualang village?, (2) What is the impact of the matapu activity initiated by the youth of Watualang village?. This journal uses a descriptive qualitative method. The results of the study revealed that the existence of tambourine art was still maintained in the form of an activity called "Matapu". Matapu became the integration of tambourine art and youth in Watualang village by implying pure tambourine art as a medium for syiar, da'wah, and interpretation of poetry/poetry. This is an encouragement for the youth of Watualang village to continue to perpetuate the wealth of the archipelago's arts in carrying out Islamic da'wah jihad as well as efforts to embrace the predicate of faith.  Keywords: tambourine art, Islamic da'wah, youth in Watualang village